Open ocean regimes of relative dispersion - Ollitrault, Michel; Gabillet, Céline; Colin De Verdiere, Alain (Journal of Fluid Mechanics, 2005)
As two fluid particles separate in time, the entire spectrum of eddy motions is being sampled from the smallest to the largest scales. In large-scale geophysical systems for which the Earth rotation is important, it has been conjectured that the relative diffusivity should vary respectively as D2 and D4/3 for distances respectively smaller and larger than a well-defined forcing scale of the order of the internal Rossby radius (with D the r.m.s. separation distance). Particle paths data from a mid-latitude float experiment in the central part of the North Atlantic appear to support these statements partly: two particles initially separated by a few km within two distinct clusters west and east of the mid-Atlantic ridge, statistically dispersed following a Richardson regime (D2∼t3 asymptotically) for r.m.s. separation distances between 40 and 300 km, in agreement with a D4/3 law. At early times, and for smaller separation distances, an exponential growth, in agreement with a D2 law, was briefly observed but only for the eastern cluster (with an e-folding time around 6 days). After a few months or separation distances greater than 300 km, the relative dispersion slowed down naturally to the Taylor absolute dispersion regime. International audience As two fluid particles separate in time, the entire spectrum of eddy motions is being sampled from the smallest to the largest scales. In large-scale geophysical systems for which the Earth rotation is important, it has been conjectured that the relative diffusivity should vary respectively as D2 and D4/3 for distances respectively smaller and larger than a well-defined forcing scale of the order of the internal Rossby radius (with D the r.m.s. separation distance). Particle paths data from a mid-latitude float experiment in the central part of the North Atlantic appear to support these statements partly: two particles initially separated by a few km within two distinct clusters west and east of the mid-Atlantic ridge, statistically dispersed following a Richardson ...